NOISE AS THE IMPACT OF TRADING MECHANISM AND PERIODIC CLEARING PROCEDURES: SUBSTANTIVE EVIDENCE FROM INDONESIA STOCK EXCHANGE - Sumiyana, Sumiyana (Journal of Indonesian Economy and Business, 2009)
Sumiyana (2007b) investigates that noises occurred in Indonesia Stock Exchange.Â Especially, Sumiyanasâ research concludes that noise over trading and nontrading period,Â along with overnight and lunch break nontrading session, and the first and second tradingÂ session, had occurred. However, Sumiyanaâs research does not identify who areÂ responsible for the noise. This research used intraday data in Indonesia Stock Exchange.Â Samples of the data are the firms consecutively listed in LQ 45 indexes for the year ofÂ 2004-2006.This research attempts to identify who are responsible for the noise. This researchÂ studies effects of trading mechanism and clearing mechanism on the stock returnÂ behaviour. Finally, this research is enabling to differentiate the effect of tradingÂ mechanism from the effect of clearing mechanism. This research concludes that periodicclearing procedure at the beginning of the trading period is noisy. Therefore, this researchÂ suggests that trading mechanism in Indonesia Stock Exchange is inefficient. This researchÂ also hopefully recommends shifting from the periodic to continuous trading mechanism.Keywords: Intraday data, trading mechanism, trading and nontrading periods, stockÂ return behaviour, noise, negative autocorrelation, clearing mechanism,Â periodic clearing procedure.